Images of Women's Power in Contemporary Canadian Fiction by Women - Beran, Carol L. (Studies in Canadian Literature, 1990)
Since the publication of Margaret Atwood's Survival in 1972, an enhanced awareness of victimization and power has been reflected by many Canadian women writers of fiction who have presented complex images of women as powerful. Aritha Van Herk's Judith and The Tent Peg take a strident feminist stance, presenting images in which women are seen to have androgynous power, power combined from men's and women's traditional sources of power; for Van Herk, freedom of choice seems to be the ultimate power. Alice Munro, in her short stories "The Beggar Maid," "Simon's Luck," and "Lichen," takes us beyond the issue of male versus female power by presenting images in which forces outside the control of men or women have the ultimate control, levelling the power struggle to an insignificance in the larger scheme of things while attributing great power to artistic creation -- a human being's ability to liken. Atwood's The Handmaid's Tale and Cat's Eye see a woman's power in terms of her ability to voice her life and emotions so as to win an emotional response; because the power to feel and to create feeling is for Atwood's heroines woman's true power, artistic creation becomes the symbol of woman's greatest power.